2020
DOI: 10.1111/jcpe.13251
|View full text |Cite
|
Sign up to set email alerts
|

Association of prosthetic features and peri‐implantitis: A cross‐sectional study

Abstract: Objective: To identify the influence of prosthetic features through a comprehensive analysis with other known risk factors. Materials and methods:A total of 169 patients (n = implants: 349) was retrospectively included in the present study. Peri-implantitis was diagnosed based on periimplant bone loss and probing depth. Using radiographs taken 1 and 5 years following prosthesis insertion, the following features were determined: peri-implant marginal bone loss (MBL), emergence angle (EA), emergence profile (EP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
224
3
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(257 citation statements)
references
References 27 publications
11
224
3
3
Order By: Relevance
“…Data from this study also found that, during the first year after the development of peri‐implantitis, implants with restoration emergence angles of >30° had around 1.74 mm more peri‐implant bone loss than when restoration emergence angles were ≤30°. This is in support of findings from other studies 23,24 . Katafuchi et al.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Data from this study also found that, during the first year after the development of peri‐implantitis, implants with restoration emergence angles of >30° had around 1.74 mm more peri‐implant bone loss than when restoration emergence angles were ≤30°. This is in support of findings from other studies 23,24 . Katafuchi et al.…”
Section: Discussionsupporting
confidence: 93%
“…Patients having factors such as a history of severe periodontitis, poor plaque control, and no regular maintenance care after implant therapy have been shown to be more prone to this disease 21 . Other factors such as implant position, smoking, diabetes, the presence of periodontitis at time of placement, restoration emergence angle, amount of keratinized mucosa, presence of residual cement, and titanium particles, have also been linked to peri‐implantitis but require more evidence 23–30 . However, only little importance has been given to the factors that may increase the progression of peri‐implant bone loss once peri‐implantitis has developed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An implant splinted to both a mesial and distal adjacent implant has a higher risk of peri-implantitis. 24 Cement causes roughness, favors bacterial attachment and foreign body reactions, and results in peri-implantitis. Removing the cement results in the resolution of inflammation in a few days to weeks and can be done using a closed procedure (dental endoscope) or open surgical flap procedure.…”
Section: Etiologies and Risk Indicators Of Peri-implant Diseasesmentioning
confidence: 99%